2021
DOI: 10.1101/2021.07.13.452155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of reading experience in atypical cortical tracking of speech and speech-in-noise in dyslexia

Abstract: Dyslexia is a frequent developmental disorder in which reading acquisition is delayed and that is usually associated with difficulties understanding speech in noise. At the neuronal level, children with dyslexia were reported to display abnormal cortical tracking of speech (CTS) at phrasal rate. Here, we aimed to determine if abnormal tracking is a cause or a consequence of dyslexia and if it is modulated by the severity of dyslexia or the presence of acoustic noise. We included 26 school-age children with dys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(128 reference statements)
2
0
0
Order By: Relevance
“…We then retained the mean of this reconstruction accuracy, leaving us with one value for all combinations of subjects, conditions, hemispheres, and frequencies of interest. Note that, as documented in previous studies ( Destoky, 2020 , Destoky et al, 2022 ), most of the 73 youngest participants of the present study showed significant CTS.…”
Section: Methodssupporting
confidence: 88%
“…We then retained the mean of this reconstruction accuracy, leaving us with one value for all combinations of subjects, conditions, hemispheres, and frequencies of interest. Note that, as documented in previous studies ( Destoky, 2020 , Destoky et al, 2022 ), most of the 73 youngest participants of the present study showed significant CTS.…”
Section: Methodssupporting
confidence: 88%
“…We then retained the mean of this reconstruction accuracy, leaving us with one value for all combinations of subjects, conditions, hemispheres, and frequencies of interest. Note that, as documented in previous studies (Destoky et al, 2020(Destoky et al, , 2022, most of the 73 youngest participants of the present study showed significant CTS.…”
Section: Cts Quantificationsupporting
confidence: 88%